2017
DOI: 10.1109/jphotov.2017.2706420
|View full text |Cite
|
Sign up to set email alerts
|

Minority Carrier Lifetime Estimation by Photoconductance Decay for Silicon Wafers Immersed in HF

Abstract: The measurement of minority carrier bulk lifetimes of Si wafers immersed in HF is known to have an immersion time dependence, which is specially strong for high lifetime wafers and can vary significantly for different surface treatments performed previously. These complications can make the lifetime measurement become difficult to interpret and inaccurate. Therefore, a method for extracting the bulk lifetime from the measured curves of lifetime versus immersion time is suggested. A model of the reaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(48 reference statements)
0
5
0
2
Order By: Relevance
“…In this regard, temporary passivation techniques which can passivate such surfaces are of interest in terms of material properties and surface roughness/ability to passivate. The lowest reported S for textured silicon wafers is 1.9 cm s −1 , once accounting for the additional surface area (1.73) . Baker‐Finch examined the dependence of S on the (111) surface area proportion, and found that S increased from ≈1 cm s −1 to 4–5 cm s −1 when the (111) proportion was increased from 0.4 to 1 respectively .…”
Section: Types Of Temporary Surface Passivationmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, temporary passivation techniques which can passivate such surfaces are of interest in terms of material properties and surface roughness/ability to passivate. The lowest reported S for textured silicon wafers is 1.9 cm s −1 , once accounting for the additional surface area (1.73) . Baker‐Finch examined the dependence of S on the (111) surface area proportion, and found that S increased from ≈1 cm s −1 to 4–5 cm s −1 when the (111) proportion was increased from 0.4 to 1 respectively .…”
Section: Types Of Temporary Surface Passivationmentioning
confidence: 99%
“…While HF based techniques in general provide the highest level of surface passivation (see Figure ), the instability of the passivation whilst silicon wafers are immersed in HF is undesirable for long term measurements. Recently, Razera et al examined the time dependence of silicon wafers immersed in 48% HF, and demonstrated that for planar (100) silicon wafers, the lifetime decays steadily for the first 6 min and then stabilises beyond this time. It was proposed that the initial high lifetime at t = 0 min represents a fluorine passivated surface, while for t > 6 min the passivation is attributed to hydrogen termination of silicon surface states, resulting in a lower, but stable surface lifetime .…”
Section: Processing Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure a shows the effective carrier lifetime ( τ eff ) of p‐Si wafers coated with and without Ta 2 O 5 films. Note that the bare c‐Si wafer has a moderate surface passivation provided by the HF treatment, [ 24 ] with the measured τ eff of 36.4 µs at the injection concentration of 1 × 10 15 cm −3 . The τ eff is increased to 66.7 µs after the deposition of Ta 2 O 5 films, and it is further improved to 90.4 µs with the introduction of SiO 2 interfacial layer, exhibiting a high surface passivation quality for p‐Si wafers.…”
Section: Resultsmentioning
confidence: 99%